INTEGRATED PET-CT SCAN IN THE STAGING OF NON SMALL CELL LUNG CANCER - Surya Negara S, I Made Ngurah Agus (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Lung cancer is a common disease and is a leading cause of death in many countries. The most kind of lung cancer was Non Small Cell Lung Cancer. The management of lung cancer is directed by an optimal staging of the tumour. On 1998, integrated positron emission tomography (PET)-computed tomography (CT) was published. PET-CT is an anatomo-metabolic imaging modality that has recently been introduced to clinical practice and combines two different techniques: CT, which provides very detailed anatomic information; and PET, which provides metabolic information. One of the advantages of PET/CT is the improved image interpretation. There wasbetter results for PET/CT in the staging of non small cell lung cancer in comparison with CT nor PET alone. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: positron emission tomography – computed tomography, non small cell lung cancer, staging